Sistem Informasi Promosi Berbasis Web Sekolah Menengah Kejuruan Veteran - Wardani, Muhammad; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2023)
Currently the school seeks an educational institution that is able to serve the community well, especially in terms of delivering information to student and the public. During this Notice of school information is still done manually, mostly still taped to the latest information dipapan announcement, through the speaker mounted each class, and still using information media such as facebook a promotional media to the public. Therefore, in this Studi conducted a needs assessment to produce the school website by using modeling UML (Unified Markup Language) usecase diagram, activity diagram, dan class diagram. Utilization of the website in the development of competence and quality of the school is the right thing because the website is very interactive media and dynamic to broaden as well as to the existence of self. Implementation of information systems based school website can be accessed anytime and anywhere via the internet. Website school can overcome the problems in the delivery of information and the promotion of school, which is still done manually. The results of this Studi are in the form of a web-based promotional information system design that can help Veteran Vocational Schools in overcoming the problems they face.